Method for preparing mica composite insulation paper by using modified aramid fibrid
Through the uniform mixing of modified aramid precipitated fibers and nanofibrilized cellulose and the use of cross-linked reinforced fibers, the insufficient performance of mica paper under high temperature and high load conditions is solved, and the breakdown voltage and heat are significantly improved Stability meets the high requirements of modern power equipment.
Patent Information
- Application Number
- CN202411393486.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing mica paper lacks performance under high temperature and high load conditions, poor bonding strength and poor compatibility, resulting in unstable breakdown voltage, high dielectric loss and poor aging resistance, making it difficult to meet the high level of modern power equipment. Require.
Modified aramid precipitation fibers are uniformly mixed with nanofibrilized cellulose, modified modifiers and crosslinked reinforcement fibers are added, and mica paper layer is prepared by solvent precipitation and high-frequency ultrasonic method, and surface roughening is carried out. Hot pressing to form composite insulating paper.
It improves the breakdown voltage stability of mica paper, reduces dielectric loss, significantly improves mechanical properties and thermal stability, and meets the higher requirements of modern power equipment for insulating materials.
Abstract
Description
Technical Field
[0001] The invention relates to the field of insulating mica products, in particular to a method for preparing mica composite insulating paper by utilizing modified aramid fibrillation. Background Art
[0002] Mica paper is a paper-like material made of mica flakes through crushing, pulping, papermaking and other processes. It has good electrical insulation, high temperature resistance, corrosion resistance and high mechanical strength. Due to its unique properties, mica paper has important application value in industry and is widely used in electronics, electrical, aerospace and other fields. It is used as an insulating material in electrical equipment such as motors, transformers, capacitors, etc. It can also be used to manufacture refractory materials and high-temperature insulation materials.
[0003] With the development of the electric power industry, modern power generation equipment and transmission equipment are gradually developing towards high voltage and large capacity, which puts forward higher requirements on the high temperature tolerance, strength performance and insulation performance of electrical insulation materials. Although the existing mica paper meets these requirements to a certain extent, there is still room for improvement in performance. For example, most of the existing mica papers use ordinary epoxy resin modified or ordinary linear polyester resin as binders during molding, and the bonding strength is not high enough and the compatibility is poor. The prepared mica paper has low mica weight, easy to fall off, low breakdown voltage, and high dielectric loss, which leads to high heat generation and poor aging resistance of the motor. If the performance of mica paper is further improved so that it can operate reliably for a long time under harsh conditions such as high temperature and high load, the application scope of mica paper will be further improved and the operation and maintenance costs of related companies will be reduced.
[0004] In order to achieve the above technical objectives, natural fibers or ordinary synthetic fibers are usually used as reinforcing materials to be mixed into mica materials to improve the performance of mica paper. Aramid fibers are mainly used to improve the mechanical strength, heat resistance, electrical insulation and dimensional stability of mica paper. However, aramid fibers have poor compatibility with mica materials when combined with mica materials, which makes it difficult to evenly disperse aramid fibers in mica materials during actual applications. This uneven dispersion state will have a negative impact on the overall performance of mica paper, which is specifically manifested in the instability of breakdown voltage, increase in dielectric loss and weather resistance defects. In addition, due to the high cost of aramid fibers, their use in mica paper is limited, which affects the performance improvement of the final product. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a method for preparing mica composite insulating paper by using modified aramid fibrids, so as to solve the shortcomings of the above-mentioned background technology.
[0006] The technical problem solved by the present invention is achieved by adopting the following technical solutions:
[0007] A method for preparing mica composite insulating paper by using modified aramid fibrids, specifically comprising the following steps:
[0008] S1. preparing modified aramid fiber: dissolving aramid fiber by using a solvent to obtain an aramid polymer dissolved in the solvent; and adding a modifying agent to modify the dissolved aramid polymer after the dissolution;
[0009] The chemical formula of the modified modifier is RSi(OR')3, wherein R is an organic group containing an amino group, an epoxy group or a vinyl group, and R' is a methyl group or an ethyl group; the amount of the modified modifier is 0.1-0.3% of the mass of the aramid fiber, and the treatment time is 1-3 hours;
[0010] After the treatment is completed, the modified aramid polymer solution is added to a precipitating agent to precipitate the aramid polymer to form modified aramid fibrids;
[0011] S2, preparing a modified mica paper layer: uniformly mixing the prepared modified aramid fiber and nanofibrillated cellulose in a mass ratio of 1:1, adding water and a dispersant, and treating them into a stable suspension; adding mica material and resin material to the suspension to prepare mica pulp; papermaking the prepared mica pulp through a papermaking machine to form wet paper sheets, and drying the formed wet paper sheets to obtain dry paper sheets, which are the modified mica paper layers;
[0012] The parameters of the modified aramid fibrid and the nanofibrillated cellulose are:
[0013] The diameter of the modified aramid fibrids ranges from 300 to 500 nm and the length ranges from 1 to 10 mm;
[0014] The diameter of nanofibrillated cellulose ranges from 10 to 100 nm and the length is 0.5 to 5 mm;
[0015] In the pulping stage of mica pulp, the amount of modified aramid fiber in the mica pulp is controlled, and the amount of modified aramid fiber is based on 5-9% of the mass of the dry paper sheet obtained after forming;
[0016] S3, preparing mica composite insulating paper: performing surface roughening treatment on one or both sides of the modified mica paper layer, and applying glue on the rough surface after the roughening treatment;
[0017] The sizing material used in the sizing is uniformly dispersed with cross-linked reinforcing fibers, the cross-linked reinforcing fibers are polyimide fibers and / or aramid fibers, and the amount of the cross-linked reinforcing fibers added is 7-15% of the mass of the sizing material;
[0018] Finished mica paper is used as the surface layer to be laminated on the surface of the adhesive layer, and then the finished mica paper and the modified mica paper are laminated and formed into one by hot pressing. The hot pressed paper sheets are cut and packaged to obtain finished composite insulating paper.
[0019] As a further limitation, in step S1, the solvent used to dissolve the aramid fiber is one or a combination of concentrated sulfuric acid, N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO).
[0020] As a further limitation, in step S1, the precipitating agent used is a saturated solution of ammonium sulfate or a saturated solution of sodium chloride or an alcohol precipitating agent; the alcohol precipitating agent is one or a combination of methanol, ethanol, and isopropanol.
[0021] As a further limitation, in step S2, the dispersant used is polyvinyl alcohol (PVA) or sodium carboxymethyl cellulose (CMC), and the amount thereof is 0.1% to 1% of the total mass of the suspension.
[0022] As a further limitation, in step S2, the method for treating the mixture of modified aramid fibrids and nanofibrillated cellulose, water and dispersant into a stable suspension is a high-frequency ultrasonic method, and the specific operation is:
[0023] The uniformly mixed suspension of modified aramid fibrils and nanofibrillated cellulose is placed in an ultrasonic generator, the ultrasonic frequency is set to 80-120kHz, the power is 600-1000W, and the treatment is carried out for 20-30 minutes, so that the cellulose fibers and modified aramid fibrils are uniformly dispersed in water through the cavitation effect and mechanical vibration of the ultrasound to form a stable suspension.
[0024] As a further limitation, in step S2, when preparing mica pulp, refer to the mica paper pulping process flow, and control the content of mica material in the mica pulp to 55-70% of the total weight of the pulp, and the mass proportion of fine-particle mica material with a particle size of 70-200 μm in the mica material is ≥35%.
[0025] As a further limitation, in step S2, when the formed wet paper sheet is dried, the drying temperature is set to 100-150°C and the drying time is set to 1-3 hours.
[0026] As a further limitation, the resin material used in step S2 is epoxy resin, and the amount thereof is 5-15% of the total mass of the mica pulp.
[0027] As a further limitation, the preparation method of the rubber material used in step S3 is:
[0028] The matrix material is prepared by compounding bisphenol A epoxy resin or bisphenol F epoxy resin with an epoxy equivalent of ≤200 g / mol with polyetheretherketone in a ratio of 3:1 to 4:1, and then mixing them in a mass ratio of matrix material: solvent = 1:1 to 1:1.5 using one of toluene, xylene, butanone, butanol, acetone and ethyl acetate as a solvent.
[0029] As a further limitation, in step S3, the surface roughening treatment method is contact surface friction treatment or vibration brush treatment, and during the treatment, it is based on the observation that fibers can be seen through the paper surface with the naked eye.
[0030] As a further limitation, in step S3, the parameter indicators of the finished mica paper as the surface layer are: thickness 0.05-0.30 mm, basis weight 50-200 g / m 2 , breakdown voltage ≥ 10KV, dielectric loss tested at 1MHz ≤ 0.01;
[0031] The sum of the thickness of the finished mica paper as the surface layer is 1 to 2.5 times the thickness of the modified mica paper layer.
[0032] As a further limitation, the diameter of the cross-linked reinforcing fibers added to the rubber compound in step S3 is in the range of 10 to 100 nm and the length is in the range of 0.5 to 5 mm.
[0033] As a further limitation, nano thermally conductive particles are also added to the rubber compound in step S3, and the nano thermally conductive particles are one or a combination of aluminum oxide, titanium oxide, zinc oxide, boron oxide, and boron nitride, and have a particle size of 30 to 100 nm. The mass ratio of the nano thermally conductive particles added to the rubber compound is 0.5 to 3%, and the nano thermally conductive particles are uniformly dispersed in the rubber compound.
[0034] As a further limitation, when performing hot pressing treatment in step S3, the temperature of the hot pressing equipment is set to 120-180°C, and the pressure is set to 0.5-1.5 MPa. During the hot pressing process, the temperature and pressure are ensured to be evenly distributed, and the hot pressing time lasts for 10-30 minutes.
[0035] Beneficial effects: The method of the present invention uses a specific modification modifier to precipitate and modify aramid fibers before preparing mica composite insulating paper to obtain modified aramid precipitated fibers with good compatibility with mica powder, thereby achieving uniform dispersion of the fibers in the mica material; this not only improves the breakdown voltage stability of the mica paper and reduces the dielectric loss; it also combines the hot-pressing composite of layers with cross-linked reinforcing fiber adhesive to form a good interface bond through spatial cross-linking between the modified aramid precipitated fibers and the cross-linked reinforcing fibers in the adhesive, significantly improving the mechanical properties and thermal stability of the composite material and the weather resistance of the paper-based insulating material, thereby improving the overall performance of the mica paper and meeting the higher requirements of modern power equipment for insulating materials. DETAILED DESCRIPTION
[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0037] In the following embodiments, it will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as the meaning in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless defined as herein.
[0038] Example 1: In the example, the mica composite insulating paper is prepared in the following manner:
[0039] First, prepare the modified aramid fiber:
[0040] Considering the stable material properties of aramid fiber precipitation itself, it is necessary to use certain specific solvents and solvent systems to treat aramid fiber, such as concentrated sulfuric acid, N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO). These solvents can destroy the intermolecular forces of aramid fiber, thereby achieving dissolution. The precipitation treatment of aramid fiber can achieve the rearrangement of aramid fiber and the improvement of crystallinity. In the aforementioned dissolution treatment process, the dissolved aramid polymer can also be modified by adding a modifying agent to make the reorganized aramid polymer show better performance. For example, in this embodiment, a small amount of a modifying agent with a chemical formula of RSi(OR')3 (wherein R is an organic group containing an amino group, an epoxy group or a vinyl group, and R' is a methyl group or an ethyl group) can be added to react with the active groups on the surface of the aramid polymer, thereby forming a modified layer on the fiber surface to enhance its compatibility with mica powder. After the modification treatment, by adding a precipitating agent to change the solubility parameter of the solution, the aramid polymer can be precipitated from the solution to form precipitated fibers, that is, modified aramid fibers with corresponding modified properties and effects are obtained.
[0041] Specifically in this embodiment, N-methylpyrrolidone (NMP) is selected as the solvent because it has good solubility for aramid fiber and is easy to remove in the subsequent treatment process. The aramid fiber is dissolved in NMP at a dosage of 7% by volume of the solvent, and then stirred at room temperature for 30 minutes to ensure that the aramid fiber is completely dissolved. Then, the modification agent NH2Si(OCH3)3 is added to the solution at a dosage of 1% by mass of the aramid fiber, and the solution is stirred for 10 minutes and then left to stand for 5 minutes for 6 cycles to promote the modification reaction.
[0042] Afterwards, a saturated solution of sodium chloride is slowly added as a precipitating agent to gradually reduce the solubility parameter of the solution, so that the modified aramid fiber is precipitated from the solution, the precipitation process is controlled, and the precipitated fiber material with a diameter range of 300 to 500 nm and a length range of 1 to 10 mm is screened out, and the desired modified aramid fiber is obtained after filtering, washing and drying. A modified layer containing amino groups is formed on the surface of the precipitated aramid fiber, and the modified layer can improve the compatibility of the fiber with mica powder, and also has good affinity with polyimide fiber and aramid fiber.
[0043] Then prepare the modified mica paper layer:
[0044] The modified aramid fibrid obtained in the preceding step is used as a raw material to prepare a modified mica paper layer. During the preparation, the modified aramid fibrid is uniformly mixed with nanofibrillated cellulose with a diameter ranging from 10 to 100 nm and a length of 0.5 to 5 mm in a mass ratio of 1:1, water and sodium carboxymethyl cellulose as a dispersant (the amount used is 0.3% of the total mass of the mixture of the modified aramid fibrid, the nanofibrillated cellulose, water and the dispersant) are added, and the mixture is treated by a high-frequency ultrasonic method, with the ultrasonic frequency set to 100 kHz and the power set to 800 W. Through the cavitation effect of the ultrasonic wave, the mechanical vibration action and the synergistic action of the dispersant, a good dispersion state is formed between the cellulose nanofibrillated fibers and the modified aramid fibrid, thereby ensuring uniform distribution of the fibers in the subsequent pulping and papermaking process. The high-frequency ultrasonic method treatment lasts for 25 minutes to form a stable suspension.
[0045] Then, the prepared suspension is used as a raw material to prepare mica pulp with mica material and resin material. The mica paper pulping process is referred to as follows:
[0046] Add mica material into the suspension and stir it preliminarily to prepare pre-slurry; control the content of mica material in mica pulp to be 60% of the total weight of pulp, and the mass proportion of fine-grained mica material with a particle size of 70-200 μm in the mica material is 40%, and the amount of suspension added is based on the mass proportion of modified aramid precipitated fibers in the dry paper sheets of modified mica paper layer after molding is 5-9%; then add epoxy resin as resin material into the pre-slurry, the amount of epoxy resin is 10% of the total mass of mica pulp, and after adding the resin material, mechanical stirring or ultrasonic treatment is performed to ensure that the fiber material is evenly dispersed, and mica pulp is obtained after even dispersion.
[0047] In the aforementioned pulping process, a high proportion of fine-grained mica material is added mainly to improve the density of the modified mica paper layer after molding, and after molding, the fine-grained mica material with smaller gaps between the paper layer structures is used as an anchor point to fix the modified aramid precipitated fibers in the system, thereby further improving the stability of the fibers in the mica paper.
[0048] The prepared mica pulp is made into paper by a rotary screen forming machine, and a preliminary formed wet paper sheet is formed by vacuum suction and pressure forming. The formed wet paper sheet is dried for 1.5 hours at 120°C in a rotary dryer to remove excess water. After drying, a dry paper sheet is obtained, which is the modified mica paper layer. During the forming period, the parameters of the rotary screen forming machine, such as the screen speed and dehydration pressure, should be adjusted according to actual needs to obtain the required paper sheet thickness and density; the uniformity and compactness of the paper sheet can also be ensured by adjusting the screen speed and vacuum degree of the rotary screen forming machine.
[0049] In this embodiment, the thickness of the final formed modified mica paper layer dry paper sheet is 0.13-0.16 mm, and the basis weight is 100 g / m 2 The breakdown voltage test value obtained by sampling test is 12KV, and the dielectric loss tested under 1MHz condition is 0.008.
[0050] Preparation of mica composite insulation paper:
[0051] In the mica composite insulation paper stage of this embodiment, it is necessary to first perform surface treatment of the modified mica paper layer and preparation of the sizing agent. The above two process stages can be performed simultaneously. Specifically in this embodiment:
[0052] When performing single-sided surface treatment on the modified mica paper layer, the contact surface friction treatment method is adopted, and the surface of the paper is gently rubbed with sandpaper until the fiber filaments are visible to the naked eye. The roughening treatment helps to improve the bonding strength between the subsequent layers and the modified mica paper layer. At the same time, the exposed modified aramid fiber precipitation can form a spatial cross-linked structure with the cross-linked reinforcing fiber during the subsequent gluing and hot pressing molding process, thereby further improving the overall performance of the composite material; after the treatment, the modified mica paper layer is placed in a dry environment to ensure that there is no moisture residue on its surface.
[0053] When preparing the sizing agent, bisphenol A epoxy resin and polyetheretherketone are compounded in a ratio of 3:1 to prepare the base material. Toluene is used as the solvent and mixed in a mass ratio of base material: solvent = 1:1.2 to obtain a uniform sizing agent solution; then cross-linked reinforcing fibers are uniformly dispersed in the sizing agent solution, and the cross-linked reinforcing fibers are polyimide fibers (diameter range is 10-100nm, length is 0.5-5mm), and the addition amount is 10% of the total mass of the base material. After adding the cross-linked reinforcing fibers to the sizing agent solution, a high-speed stirrer is used to stir at a speed of 1500 rpm for 10 minutes to ensure that the fibers are uniformly dispersed in the base material to obtain the finished sizing agent.
[0054] The roughened surface of the modified mica paper layer was used as the bonding surface, and the finished sizing material was used for sizing. After the sizing was completed, the commercially available finished mica paper (product parameters: thickness 0.3 mm, basis weight 180 g / m 2 , the breakdown voltage is 16KV, and the dielectric loss tested at 1MHz is 0.007) as the surface layer is adhered to the surface of the adhesive layer and sent to the hot pressing equipment for hot pressing treatment. The temperature of the hot pressing equipment is controlled to be 150℃, the pressure is 1MPa, and the hot pressing time lasts for 20min. During the hot pressing process, the temperature and pressure are ensured to be evenly distributed. After the hot pressing is completed, it is cut and packaged to obtain the finished composite insulating paper.
[0055] The performance parameters of the finished composite insulation paper are: thickness 0.45-0.51 mm, basis weight 280 g / m 2 , the breakdown voltage test value reached 18KV, and the dielectric loss was 0.007 at 1MHz, showing excellent electrical insulation performance. In addition, the tensile strength and tear strength of the composite insulation paper have also been significantly improved, reaching 120MPa and 15N / mm respectively, which is mainly due to the three-dimensional network structure formed by the modified aramid fiber precipitation and cross-linked reinforcing fiber in the matrix material, and the good bonding between the modified mica paper layer and the surface mica paper.
[0056] Example 2: In the example, mica composite insulating paper is prepared by the following method:
[0057] First, prepare the modified aramid fiber:
[0058] A solvent system of concentrated sulfuric acid and dimethyl sulfoxide (DMSO) with a mass concentration of 95.6% was selected as the solvent, and the aramid fiber was dissolved in the aforementioned solvent system at a doping amount of 9% by volume of the solvent, and then stirred at room temperature for 30 minutes to ensure that the aramid fiber was completely dissolved.
[0059] The modified agent is NH2(CH2)3Si(OCH3)3, and the modified agent is added into the dissolved aramid solution at a ratio of 0.15% of the mass of the aramid fiber, and stirring is continued for 1 hour.
[0060] Then, isopropanol is slowly added for precipitation treatment, precipitation parameters are controlled, and precipitated fiber materials with a diameter range of 300-500nm and a length range of 6-10mm are screened out. After filtering, washing and drying, the desired modified aramid fiber is obtained.
[0061] Preparation of modified mica paper layer:
[0062] The modified aramid fiber precipitation and nanofibrillated cellulose with a diameter range of 80 to 100 nm and a length of 0.5 to 3.0 mm are mixed uniformly in a mass ratio of 1:1 to obtain a fiber mixture, the fiber mixture is added to water to obtain a mixed solution, and polyvinyl alcohol (PVA) is added together. The polyvinyl alcohol is used as a dispersant in an amount of 0.7% of the total mass of the fiber mixture water and the dispersant. The above-mentioned mixture solution is treated by high-frequency ultrasound, with an ultrasonic frequency of 120 kHz and a power of 1200 W for 20 minutes to obtain a morphologically stable suspension.
[0063] The mica slurry is prepared in the same manner as in the embodiment, that is, firstly, the mica material is added to the suspension to prepare the pre-slurry; then, the epoxy resin is added to the pre-slurry, and the mica pulp is obtained after uniform dispersion. In this embodiment, the content of the mica material in the mica pulp is 72% of the total weight of the pulp, and the mass proportion of the fine-grained mica material with a particle size of 70 to 200 μm in the mica material is 38%; the amount of the suspension added is based on the mass proportion of the modified aramid fiber in the dry paper sheet of the modified mica paper layer after molding is 5 to 9%; and the amount of the epoxy resin is 7% of the total mass of the mica pulp.
[0064] Then, the prepared mica pulp is used to make mica paper and obtain a modified mica paper layer dry paper sheet.
[0065] In this embodiment, the thickness of the final formed modified mica paper layer dry paper sheet is 0.13-0.16 mm, and the basis weight is 120 g / m 2 The breakdown voltage test value obtained by sampling test is 12KV, and the dielectric loss tested under 1MHz condition is 0.0076.
[0066] Preparation of mica composite insulation paper:
[0067] When preparing mica composite insulating paper, a single-side surface roughening treatment is performed on the modified mica paper layer using a vibrating brush until fiber filaments are visible to the naked eye.
[0068] When preparing the rubber compound, bisphenol A epoxy resin and polyetheretherketone are compounded in a ratio of 4:1 to form a base material. Toluene is used as a solvent and mixed in a mass ratio of base material: solvent = 1:1.5 to obtain a uniform rubber compound solution; cross-linked reinforcing fibers with a diameter of 50 to 100 nm and a length of 2 to 5 mm are added to the rubber compound, and the addition amount is 1% of the rubber compound mass; at the same time, alumina nano-thermal conductive particles with a particle size of 50 nm are added, and the addition mass ratio is 1.5% to ensure uniform dispersion in the rubber compound.
[0069] According to the method of Example 1, commercially available finished mica paper is attached to the rough surface of the modified mica paper layer. The product parameters of the commercially available finished mica paper are: thickness 0.3 mm, basis weight 160 g / m 2 , the breakdown voltage is 15KV, and the dielectric loss tested at 1MHz is 0.008.
[0070] The laminated materials were sent to a hot pressing device for hot pressing treatment. The temperature of the hot pressing device was set to 150° C. and the pressure was set to 1 MPa with the same parameters as in Example 1. The hot pressing time lasted for 20 minutes, and a finished composite insulating paper was obtained.
[0071] The performance parameters of the finished composite insulating paper obtained under the process conditions of Example 2 are: thickness of 0.46-0.50 mm, basis weight of 270 g / m 2 , the breakdown voltage test value reaches 17KV, and the dielectric loss is 0.0075 at 1MHz. Compared with Example 1, although the breakdown voltage is slightly lower, the dielectric loss is slightly increased, but still remains at a low level, showing good electrical insulation performance. In addition, the tensile strength and tear strength of the composite insulating paper are also significantly improved, reaching 115MPa and 14N / mm respectively.
[0072] In addition, in Example 2, by introducing alumina nano-thermal conductive particles, the thermal conductivity of the composite insulating paper is further improved, and its thermal conductivity is improved by 15% and 10% respectively compared with the commercially available mica paper of the same thickness and the composite paper-based insulating material prepared by the technical solution of Example 1. This makes the composite insulating paper have better thermal stability under high voltage and high temperature environment, thereby extending the service life of electrical equipment and improving its reliability.
[0073] Embodiment 3,
[0074] In the preparation method of Example 3, the mica composite insulating paper adopts the same process treatment method as in Example 1 in the early stage of the preparation stage to obtain the same modified mica paper layer dry paper sheet as in Example 1 (corresponding technical parameters: thickness 0.13-0.16 mm, basis weight 100 g / m 2 The breakdown voltage test value obtained by sampling test is 12KV, and the dielectric loss tested at 1MHz is 0.008) and the rubber.
[0075] The only difference between Example 3 and Example 1 is that the surface roughening treatment of the dry paper sheet of the modified mica paper layer is double-sided treatment, and the treatment method is the same, both using a contact surface friction treatment method, using sandpaper to gently rub the surface of the paper until the fiber filaments are visible to the naked eye.
[0076] The parameters of the commercially available finished mica paper used as the surface layer are 0.15 mm thick and 100 g / m 2 The breakdown voltage is 13KV, and the dielectric loss is 0.006 under 1MHz. The modified mica paper layer dry paper sheet is double-sidedly laminated with the commercial finished mica paper and then hot pressed. The hot pressing process parameters are the same as those of Example 1, that is, the hot pressing temperature is 150°C, the hot pressing pressure is 1MPa, and the hot pressing time lasts for 20min. After the hot pressing is completed, post-processing is performed to obtain a finished composite insulating paper.
[0077] In this embodiment, the performance parameters of the finished composite insulating paper are: thickness of 0.47-0.52 mm, basis weight of 260 g / m 2 The breakdown voltage test value reaches 14KV, and the dielectric loss is 0.007 at 1MHz. Compared with the first and second embodiments, although the breakdown voltage is slightly lower, the dielectric loss remains at a low level, showing good electrical insulation performance.
[0078] In addition, after the double-sided roughening treatment, the tensile strength and tear strength of the composite insulating paper of Example 3 are further improved, reaching 120 MPa and 15 N / mm respectively. This makes the composite insulating paper more excellent in mechanical properties and can better adapt to the mechanical stress that may be encountered by electrical equipment during operation.
[0079] In terms of thermal stability, the composite insulating paper of Example 3 also performs well. Since the double-sided roughening treatment increases the contact area with the adhesive, the bonding between the adhesive and the paper layer is tighter during the hot pressing process, thereby improving the overall thermal stability of the material. Under high temperature conditions, the thermal conductivity of the composite insulating paper is improved by 10% and -5% respectively compared to Example 1 and Example 2. The thermal conductivity is improved compared to Example 1, but slightly worse than Example 2 with thermal conductive particles. This makes the composite insulating paper have better thermal stability under high voltage and high temperature environments, thereby further extending the service life of electrical equipment and improving its reliability.
[0080] In summary, the composite insulating paper of Example 3 achieves significant improvement in mechanical properties and thermal stability through double-sided roughening and optimized hot pressing process while maintaining good electrical insulation performance. The composite insulating paper is not only suitable for high-voltage electrical equipment, but also can cope with complex mechanical stress and high temperature environment, providing a strong guarantee for the long-term stable operation of electrical equipment.
[0081] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing mica composite insulating paper using modified aramid fiber precipitation, characterized in that: The steps include: S1. preparing modified aramid fiber: dissolving aramid fiber by using a solvent to obtain an aramid polymer dissolved in the solvent; and adding a modifying agent to modify the dissolved aramid polymer after the dissolution; The chemical formula of the modified modifier is RSi(OR')3, wherein R is an organic group containing an amino group, an epoxy group or a vinyl group, and R' is a methyl group or an ethyl group; the amount of the modified modifier is 0.1-0.3% of the mass of the aramid fiber, and the treatment time is 1-3 hours; After the treatment is completed, the modified aramid polymer solution is added to a precipitating agent to precipitate the aramid polymer to form modified aramid fibrids; S2. Preparing a modified mica paper layer: uniformly mixing the prepared modified aramid fibrils and nanofibrillated cellulose in a mass ratio of 1:1, adding water and a dispersant, and processing into a stable suspension; Adding mica material and resin material into the suspension to prepare mica pulp; papermaking the prepared mica pulp through a papermaking machine to form wet paper sheets, drying the formed wet paper sheets to obtain dry paper sheets, which are modified mica paper layers; The parameters of the modified aramid fibrid and the nanofibrillated cellulose are: The diameter of the modified aramid fibrids ranges from 300 to 500 nm and the length ranges from 1 to 10 mm; The diameter of nanofibrillated cellulose ranges from 10 to 100 nm and the length is 0.5 to 5 mm; In the pulping stage of mica pulp, the amount of modified aramid fiber in the mica pulp is controlled, and the amount of modified aramid fiber is based on 5-9% of the mass of the dry paper sheet obtained after forming; S3, preparing mica composite insulating paper: performing surface roughening treatment on one or both sides of the modified mica paper layer, and applying glue on the rough surface after the roughening treatment; The sizing material used in the sizing is uniformly dispersed with cross-linked reinforcing fibers, the cross-linked reinforcing fibers are polyimide fibers and / or aramid fibers, the diameter of the cross-linked reinforcing fibers is in the range of 10 to 100 nm, and the length is in the range of 0.5 to 5 mm; the addition amount of the cross-linked reinforcing fibers is 7 to 15% of the mass of the sizing material; Finished mica paper is used as the surface layer to be laminated on the surface of the adhesive layer, and then the finished mica paper and the modified mica paper are laminated and formed into one by hot pressing. The hot pressed paper sheets are cut and packaged to obtain finished composite insulating paper.
2. The method for preparing mica composite insulating paper using modified aramid fibrid according to claim 1, characterized in that: In step S1, the solvent used to dissolve the aramid fiber is one or a combination of concentrated sulfuric acid, N-methylpyrrolidone, and dimethyl sulfoxide.
3. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: The precipitating agent used in step S1 is a saturated solution of ammonium sulfate or a saturated solution of sodium chloride or an alcohol precipitating agent; the alcohol precipitating agent is one or a combination of methanol, ethanol and isopropanol.
4. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: The dispersant used in step S2 is polyvinyl alcohol or sodium carboxymethyl cellulose, and the amount thereof is 0.1% to 1% of the total mass of the suspension.
5. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: In step S2, the method for treating the mixture of modified aramid fibrids, nanofibrillated cellulose, water and dispersant into a stable suspension is a high-frequency ultrasonic method, and the specific operation is as follows: The uniformly mixed suspension of modified aramid fibrils and nanofibrillated cellulose is placed in an ultrasonic generator, the ultrasonic frequency is set to 80-120kHz, the power is 600-1000W, and the treatment is carried out for 20-30 minutes, so that the cellulose fibers and modified aramid fibrils are uniformly dispersed in water through the cavitation effect and mechanical vibration of the ultrasound to form a stable suspension.
6. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: In step S2, mica pulp is prepared by referring to the mica paper pulping process, and the content of mica material in the mica pulp is controlled to be 55-70% of the total weight of the pulp, and the mass proportion of fine-particle mica material with a particle size of 70-200 μm in the mica material is ≥35%.
7. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: The preparation method of the rubber material used in step S3 is: The matrix material is prepared by compounding bisphenol A epoxy resin or bisphenol F epoxy resin with an epoxy equivalent of ≤200 g / mol with polyetheretherketone in a ratio of 3:1 to 4:1, and then mixing them in a mass ratio of matrix material: solvent = 1:1 to 1:1.5 using one of toluene, xylene, butanone, butanol, acetone and ethyl acetate as a solvent.
8. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: In step S3, the surface roughening treatment method is contact surface friction treatment or vibration brush treatment, and the treatment is based on the observation that fibers can be seen through the paper surface with the naked eye.
9. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: In step S3, the parameters of the finished mica paper as the surface layer are: thickness 0.05-0.30 mm, basis weight 50-200 g / m 2 , breakdown voltage ≥ 10KV, dielectric loss tested at 1MHz ≤ 0.01; The sum of the thickness of the finished mica paper as the surface layer is 1 to 2.5 times the thickness of the modified mica paper layer.
10. The method for preparing mica composite insulating paper by using modified aramid fibrid according to claim 1, characterized in that: Nano thermally conductive particles are also added to the rubber compound in step S3. The nano thermally conductive particles are one or a combination of aluminum oxide, titanium oxide, zinc oxide, boron oxide, and boron nitride, and have a particle size of 30 to 100 nm. The mass ratio of the nano thermally conductive particles added to the rubber compound is 0.5 to 3%, and the nano thermally conductive particles are uniformly dispersed in the rubber compound.
Citation Information
Patent Citations
Mica composite material of internally-increased short fiber for new energy automobile and preparation process of mica composite material
CN114163777A
Aramid fibrid and preparation method and application thereof
CN115110171A
Composite mica paper
CN115341410A
Corona-resistant plastic-based composite material and preparation method therefor, corona-resistant composite sheet, and stator of electric motor
WO2024141111A1